Comparison of V-Y Advancement Flap with Reverse Sural Flap for Coverage of Posterior Heel Soft Tissue Defects - Dar, Sidra Saghir; Mirza, Ali Rafique; Mir, Zameer Abbas; Bhutto, Abdul Waheed; Nasir, Gulbaz Ali (Indus Journal of Bioscience Research, 2025)
Background: Soft tissue defects of the posterior heel are difficult to manage due to high pressure load, limited local tissue, and frequent exposure of vital structures. Objective: To compare the outcomes of V-Y advancement flap and reverse sural flap for coverage of posterior heel soft tissue defects. Methodology: This randomized controlled trial was conducted at the Department of Plastic Surgery, Shaikh Zayed Hospital, Lahore, from November 2024 to April 2025. Sixty patients aged 14–60 years with posterior heel soft tissue defects were enrolled and randomized into two groups (n=30 each). Group A underwent reverse sural flap, while Group B received V-Y advancement flap. Results: The mean operative time was significantly longer in Group A (96.2 ± 14.8 min) compared to Group B (72.5 ± 11.3 min; p < 0.001). Flap necrosis occurred in 5 patients (16.7%) in Group A versus 1 patient (3.3%) in Group B (p = 0.04). Donor site disfigurement was observed in 20.0% of Group A patients but in none of Group B (p = 0.01). Other complications such as flap dehiscence, edema, congestion, and infection were more frequent in Group A but not statistically significant. By day 14, satisfactory wound healing was achieved in 86.7% of Group A and 96.7% of Group B patients (p = 0.16). Conclusion: Both flaps are effective for posterior heel reconstruction. The V-Y advancement flap offers shorter operative time, lower necrosis rates, and superior donor site cosmesis, making it preferable for small to moderate defects. The reverse sural flap remains valuable for larger or more complex heal wounds.